Reconstructing Digital Consumer Protection in Indonesia: Towards an Integrative Risk-Based Compliance Framework - Suparlan Suparlan; Apipuddin Apipuddin; Nasrullah Nasrullah; Saipul Arip Watoni; Lalu Akhmad Rizkan; Harun Azwari; Muhamad Yusup (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
The rapid expansion of Indonesia’s digital economy has transformed consumer protection from a product- and transaction-oriented issue into a broader question of digital governance, personal data security, platform responsibility, and risk-based regulatory compliance. Although existing studies have examined consumer protection, electronic commerce, and personal data protection separately, limited scholarly attention has been given to how these legal regimes can be integrated into a coherent compliance framework for digital business actors. This study aims to reconstruct digital consumer protection in Indonesia by developing an integrative risk-based compliance framework that connects consumer rights, data protection obligations, and platform accountability. Using normative juridical research with statutory and conceptual approaches, this study analyzes primary legal materials and relevant scholarly literature to assess the coherence of legal norms, the allocation of responsibility, and the adequacy of preventive and remedial mechanisms in digital transactions. The study finds that Indonesia’s digital consumer protection framework remains fragmented across several legal instruments, resulting in overlapping obligations, unclear platform liability, weak regulation of electronic standard clauses, and limited mechanisms for consumer redress in data-driven transactions. The proposed framework classifies compliance obligations according to the level of risk arising from digital business activities, including risks related to transaction asymmetry, misuse of personal data, algorithmic or platform-based control, and consumer loss recovery. The novelty of this study lies in its integration of consumer protection, personal data protection, and platform accountability into a single risk-based compliance model. Theoretically, this framework contributes to the development of digital consumer protection scholarship by shifting the analysis from sectoral regulation to integrated regulatory governance. Practically, it provides guidance for regulators, digital platforms, and business actors in designing preventive compliance systems, strengthening accountability mechanisms, and developing more effective online dispute resolution for digital consumers in Indonesia.